Combined cutting-deforming taps - Stefanova Aleksandrova, Irina (Strojniški vestnik, 2013)
Enhancement of the efficiency and quality of internal thread forming requires continuous improvements in the design of the tools used and optimization of their body geometry. A new design for cutting-tightening taps with enhanced strength and reliability for forming thread surfaces by combining the methods of cutting and plastic deformation are proposed in this paper. An experimental study of torque was carried out during thread forming employing the designed combined tool and the major factors having an effect on the tool serviceability were defined. An algorithm for designing cutting-tightening taps has been proposed, which guarantees a minimum torque in thread forming.
Keywords: combined cutting-deforming tap; kombinirano odrezovanje/preoblikovanje navoja; methods of machining; navoji; postopek obdelave; threads